Immune thrombocytopenic purpura following mRNA-SARS-CoV-2 vaccination: a case report - Lozada Ramos, Heiler; Martínez-Vega, Ruth Aralí; García, Liliana Torcoroma (Revista Cuidarte, 2024)
Highlights • Cases of autoimmune diseases have been registered after vaccination with mRNA vaccines (BNT162b2 or mRNA-1273). • A case of immune thrombocytopenic purpura following mRNA-SARS-CoV-2 without any previous reports of thrombocytopenia or other hematologic disorders is presented. • The thrombocytopenia persisted and progressed to a chronic non-bleeding condition two years after the first vaccine dose administration, with episodes of temporary recovery of platelet counts. • Considering that the incidence of secondary ITP and other hematological disorders has significantly increased due to COVID-19 vaccination, a post-vaccination hemogram check could be a useful and inexpensive follow-up measure. Introduction: Herein, it is presented a case report of a Colombian adult male patient, without any previous report of thrombocytopenia or hematological disorders, who developed a mild and chronic paucisymptomatic immune thrombocytopenic purpura, a rare complication following SARS-CoV-2 m-RNA. To the best of our knowledge, this represents the first documented case in Colombia of immune thrombocytopenic purpura associated with mRNA vaccines (BNT162b2 or mRNA-1273), with a comprehensive 2-year clinical follow-up. Case Description: The patient received the initial and second doses of the mRNA BNT162b2 vaccine in June 2021, the first booster dose in November 2021 (mRNA-1273), and the second booster dose (mRNA BNT162b2) in June 2022. Thrombocytopenia (<100 x109 platelets/L, which is the criterion to define immune thrombocytopenic purpura) was documented after the second vaccination dose and both boosters, and it improved after corticosteroid therapy. However, cycling thrombocytopenia persisted until the clinical follow-up in August 2023, with platelet count ranging from 57 to 191 x109 platelets/L (mean: 103 x109 platelets/L). Conclusion: Given that secondary immune thrombocytopenic purpura can occur following SARS-CoV-2 mRNA vaccination, systematic research to identify risk factors associated with immune thrombocytopenic purpura due to COVID-19 immunization should be conducted. How to cite this article: Lozada Ramos Heiler, Martínez-Vega Ruth Aralí, García Liliana Torcoroma. Immune thrombocytopenic purpura following mRNA-SARS-CoV-2 vaccination: A case report. Revista Cuidarte. 2024;15(2):e3799. https://doi.org/10.15649/cuidarte.3799